The influence of fraction size on the chemical composition of winter wheat flour - Tarján, Zsuzsanna; P. Barancsi, Ágnes; Mezei, Zoltán (Acta Agraria Debreceniensis, 2010)
Wheat is one of the most important cereals in the world and the bread made of its flour belongs to the everyday life of human  mankind.The Hungarian standard relating to the laboratory production of wheat flour (MSZ 6367/9-1989) does not mention the type of laboratory mill used for milling, and it only builds up some general criteria, such as: the laboratory mill should be provided  with four differently nicked barrels, a sieve with appropriate hole sizes, and also with the separated collections of the pilot flour and the bran. Our study was started at this point and the answers for the following questions were aimed to be found: do the flour patterns studied and produced with different sieving techniques, widely used in laboratory mills of the same wheat pattern show any alterations after the impact of the formula production as regards chemical constitutions. Various flours of the wheat pattern sieved with different particle sizes were studied in this experiment. In producing this pattern we used FQC109 type of mill. There were 5 different corn sizes of 250-200; 200-160; 160-125; 125-100;